Effectiveness of Reality Technique Group Counseling Against Reduction Academic Procrastination of Students at State Islamic Madrasah 1 Central Aceh - Fauza Rizki; Muhaammad Nur Wangid (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Several studies have shown that reality technique group counseling is effective for reducing academic procrastination, although it is rarely used by guidance and counseling teachers. This study aims to determine the effectiveness of reality technique group counseling in reducing academic procrastination of students of MAN 1 Aceh Tengah. This research is a quasi-experimental quantitative research with a non-equivalent control group design. Determination of the sample using purposive sampling technique. The characteristics of this research sample are students who have high academic procrastination problems, so there are 14 students, of which 7 students become the control group and 7 other students become the experimental group. The data collection instrument used the academic procrastination scale. The data analysis technique used is test Wilcoxon signed rank test. The results showed that group counseling with reality techniques was effective in reducing academic procrastination of students at MAN 1 Aceh Tengah. This can be seen from the results of the average score pretest And post test which is 45.86 higher when compared to 29.14, while based on the results of the analysis of the Wilcoxon signed ranks test the Z count results are -2.371b and the Asymp sig (2-tailed) value is 0.018 or the probability is below alpha 0.05 (0.018 ≤ 0.05) which means that there is a significant difference between the pretest and posttest scores